Brain Metastasis in Papillary Serous Adenocarcinoma of the Endometrium - Eulálio Filho, Walberto Monteiro Neiva; Fé, Taíla Sousa de Moura; Rodrigues, Rodolfo Myronn de Melo; Lima, Maria Simone Oliveira; Vieira, Sabas Carlos (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2019)
Background Most endometrial cancers (75%) are diagnosed in early stages (stages I and II), in which abnormal uterine bleeding is the most frequent clinical sign. When the diagnosis is performed in stage IV, the most common sites of metastasis are the lungs, liver and bones. Central nervous system (CNS) metastasis is a rare condition. The aim of this study is to describe a case of uterine papillary serous adenocarcinoma of the endometrium that progressed to brain and bone metastases.Case Report We present the case of a 56-year-old woman with abnormal uterine bleeding and endometrial thickened echo (1.8 cm). A hysteroscopy with biopsy was performed, which identified poor differentiated serous adenocarcinoma of the endometrium. A total abdominal hysterectomy, with pelvic and para-aortic lymphadenectomy, was performed. Analysis of the surgical specimen revealed a grade III uterine papillary serous adenocarcinoma. Adjuvant radio/chemotherapy (carboplatin and paclitaxel—six cycles) was indicated. Sixteen months after the surgery, the patient began to complain of headaches. Brain magnetic resonance imaging demonstrated an expansile mass in the right parietal lobe, suggesting a secondary hematogenous implant subsequently confirmed by biopsy. She underwent surgery for treatment of brain metastasis, followed by radiotherapy. She died 12 months after the brain metastasis diagnosis due to disease progression.Conclusion Uterine papillary serous adenocarcinoma of the endometrium has a low propensity to metastasize to the brain. To the best of our knowledge, this is the fifth documented case of uterine papillary serous adenocarcinoma of the endometrium with metastasis to the CNS.
Keywords: endometrium; serous adenocarcinoma; metastasis; brain